RESPON SISWA TERHADAP BAHAN AJAR AUDIO VISUAL DALAM KEGIATAN MENULIS TEKS BERITA - Peri Setiawan; Alfa Mitri Suhara; Raden Ika Mustika (IKIP Siliwangi, 2023)
News text learning is studied at the junior high school education level which conveys news and its delivery. However, news text learning activities are still carried out conventionally so innovation is needed in learning activities. One of them is by using audio-visual based teaching materials in news text writing activities. Audio visual media is an intermediary or display used by teachers in teaching and learning activities where the material is absorbed through sight (images) and hearing (sound). With audio-visual learning media on news text writing skills, it can make students more interested and enthusiastic in learning. News is a report of events published or broadcast in the mass media in the form of facts or ideas, consisting of the 5W+1H elements, and containing news values ​​or journalistic values. The aim of this research is to determine students' responses to the application of audio-visual based teaching materials in news text writing activities. The research method used is descriptive qualitative with a research instrument in the form of a questionnaire. Based on the results of the research that has been carried out, it is known from the results of the questionnaire that the average obtained is 80.33% in the good category. This means that it can be concluded that students respond well to the use of audio-visual teaching materials in news text writing skills.